Correlation of Neutrophil-To-Lymphocyte Ratio, Platelet-To-Lymphocyte Ratio, Platelet-To-Neutrophil Ratio, and Systemic Immune-Inflammation Index with the Severity of Pemphigus - Erliana Tantri Harsono; Agnes Sri Siswati; Shinta Trilaksmi Dewi; Fajar Waskito; Dyah Ayu Mira Oktarina (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2026)
Background: Pemphigus is a chronic autoimmune blistering disease characterized by acantholysis. Assessing disease activity is vital for optimizing therapy. While anti-desmoglein ELISA is the standard marker, its cost limits routine use in developing countries. Systemic inflammation drives the pathogenesis of pemphigus, suggesting that hematological indices—neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), platelet-to-neutrophil ratio (PNR), and systemic immune-inflammation index (SII)—may serve as accessible biomarkers.  Purpose: To evaluate the correlation between these indices and disease severity, measured by the Pemphigus Disease Area Index (PDAI), in an Indonesian population. Methods: This cross-sectional study analyzed pemphigus patients at Dr. Sardjito General Hospital, Yogyakarta. Correlations between hematological markers and PDAI scores were assessed using Spearman’s test, and diagnostic performance was evaluated via receiver operating characteristics (ROC) analysis. Result: Sixty subjects were included (68.3% female; mean age 50.17 ± 14.75 years). Pemphigus vulgaris (60%) and pemphigus foliaceus (35%) were the main subtypes; the median PDAI was 37, indicating severe disease. Significant positive correlations were observed between PDAI and NLR (r=0.467), SII (r=0.430), and PLR (r=0.275), with a negative correlation for PNR (r=–0.371). Subtype analysis showed that NLR, PNR, and SII were significantly correlated with severity specifically in pemphigus foliaceus. Furthermore, NLR demonstrated the highest predictive value. Conclusion: Simple hematological indices such as NLR, PLR, PNR, and SII show promise as non-invasive markers for assessing pemphigus severity. These parameters support cost-efficient clinical evaluation, bridging the diagnostic gap in settings where specific serological testing is inaccessible.